2013
DOI: 10.1245/s10434-013-3262-5
|View full text |Cite
|
Sign up to set email alerts
|

Low Total Lymphocyte Count Is Associated with Poor Survival in Patients with Resected Pancreatic Adenocarcinoma Receiving a GM-CSF Secreting Pancreatic Tumor Vaccine

Abstract: Background Low total lymphocyte count (TLC) and lymphocyte-to-neutrophil ratio have been found to be poor prognostic indicators in several different tumor types at various stages. Although immune-based therapies are under rapid development, it is not known whether baseline complete blood counts, particularly lymphocytes, are associated with the clinical outcomes of patients receiving immunotherapies. Methods We performed a retrospective analysis of complete blood count for 59 patients enrolled onto a phase I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…It has been detected that serum albumin is a stable predictor of prognosis during initial treatment in patients with diffuse large B cell lymphoma, and the preoperative albumin-to-globulin ratio has been verified to have predictive value for long-term mortality in nasopharyngeal carcinoma [15,16]. The peripheral lymphocyte count, as a component of the complete blood count, together with the neutrophil-to-lymphocyte ratio and platelets-to-lymphocyte ratio, has been reported to be a critical factor associated with OS in many types of cancers [17,18,19]. It is a parameter of cell-mediated immunity which is important for the host defense against cancer, and a low lymphocyte count may be associated with immune suppression indicating an inadequate immunological response.…”
Section: Discussionmentioning
confidence: 99%
“…It has been detected that serum albumin is a stable predictor of prognosis during initial treatment in patients with diffuse large B cell lymphoma, and the preoperative albumin-to-globulin ratio has been verified to have predictive value for long-term mortality in nasopharyngeal carcinoma [15,16]. The peripheral lymphocyte count, as a component of the complete blood count, together with the neutrophil-to-lymphocyte ratio and platelets-to-lymphocyte ratio, has been reported to be a critical factor associated with OS in many types of cancers [17,18,19]. It is a parameter of cell-mediated immunity which is important for the host defense against cancer, and a low lymphocyte count may be associated with immune suppression indicating an inadequate immunological response.…”
Section: Discussionmentioning
confidence: 99%
“…CD3 and CD8 were employed for tumor infiltrated lymphocytes (TIL) markers, and Image J (version Java 1.8.0_112, NIH, Bethesda, MD, USA) analysis was performed for measurement of positive staining cells. More than 1500 cells/mm 3 CD3 + or CD8 + T cells was defined as high TIL status, otherwise would be defined as low TIL, as previously reported …”
Section: Methodsmentioning
confidence: 99%
“…More than 1500 cells/mm 3 CD3 + or CD8 + T cells was defined as high TIL status, otherwise would be defined as low TIL, as previously reported. 16,17 For the ELISAs, tumor cells and CD8 + naïve T cells co-culture supernatants were collected by centrifugation and stored at −80°C.…”
Section: Immunohistochemistry and Elisamentioning
confidence: 99%
“…27 Phase I and II clinical trials of this vaccine demonstrated its safety and its ability to enhance tumor antigen (mesothelin)-specific interferon-γ (IFNγ) producing T cells in peripheral lymphocytes, which correlated with prolonged survival. 27-32 More recently, through a clinical trial of GVAX as a neoadjuvant therapy for resectable PDAs, we observed vaccine-induced tertiary lymphoid aggregates in PDAs surgically resected from the majority of patients who received the vaccine therapy two weeks prior to the surgery and also observed the infiltration of PD-L1 + cells within these lymphoid aggregates. 33 …”
Section: Introductionmentioning
confidence: 92%